2013
DOI: 10.1002/bio.2488
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid spectrofluorimetric method for determining the pharmacokinetics and metabolism of rhaponticin in rat plasma, feces and urine using a cerium probe

Abstract: Rhaponticin (RH) demonstrates a variety of pharmacological activities, including antitumor, antithrombotic and antioxidant effects. It is essential to establish a simple, rapid and reliable analytical method for determining the pharmacokinetics of RH. A simple cerium ion (Ce(3+)) probe method was developed and validated to determine RH in rat plasma, feces and urine. The fluorescence intensities of the cerium ion (Ce(3+)) were quenched by addition of RH, along with a remarkable red shift. Spectral data reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The pharmacokinetic properties of rhaponticin were examined by different studies (Zhao et al 2011 ; Sun et al 2013 , 2016 ). Rhaponticin pharmacokinetics was studied in vivo in rats after oral (100 mg/kg) and intravenous (10 mg/kg) administration.…”
Section: Plant Secondary Metabolites As Alpha-glucosidase Inhibitorsmentioning
confidence: 99%
“…The pharmacokinetic properties of rhaponticin were examined by different studies (Zhao et al 2011 ; Sun et al 2013 , 2016 ). Rhaponticin pharmacokinetics was studied in vivo in rats after oral (100 mg/kg) and intravenous (10 mg/kg) administration.…”
Section: Plant Secondary Metabolites As Alpha-glucosidase Inhibitorsmentioning
confidence: 99%
“…The pharmacokinetics of rhaponticin/rhapontigenin has been examined using various techniques, including UHPLC-Q-TOF/MS, UHPLC-DAD-MSn (Zhao et al 2012), or analysis after complexation with cerium (Ce 3? ) (Sun et al 2013) and erbium (Er 3? ) (Sun et al 2016) ions.…”
Section: Bioavailability Of Rhaponticin and Limitations Of Its Potentmentioning
confidence: 99%
“…Because of the unpredictable idea of the matrix (regularly plasma or urine) and the requirement for high affectability to take note of concentrations after low dose administration over a significant time, PK is frequently examined utilizing the fluorescence spectrometry procedure. [10][11][12] Presently, there is an interest for the utilization of high sensitivity fluorescence spectrometry for microdosing analysis, which is viewed as a promising option in substitute to animal investigation. 10,11 Pilot research in our lab indicated the native fluorescence property of RAV.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Presently, there is an interest for the utilization of high sensitivity fluorescence spectrometry for microdosing analysis, which is viewed as a promising option in substitute to animal investigation. 10,11 Pilot research in our lab indicated the native fluorescence property of RAV. The additional evaluation of this occurrence prompted the recommendation that the utilization of fluorescence spectrometry could be one of the suitable choices for the quantification of RAV in rat plasma.…”
Section: Introductionmentioning
confidence: 99%